Análisis de la aplicación alternada entre las técnicas de radio frecuencia y luz pulsada intensa (ipl) para rejuvenecimiento facial en paciente masculino de 40 años - Mosquera Parra, Diana Maritza (2025)
The study addresses the problem of facial ageing in men in their 40s, seeking an effective solution through the alternating application of radiofrequency (RF) and intense pulsed light (IPL) techniques. The main objective is to evaluate the efficacy of the combined techniques to provide solid evidence to support their aesthetic use and improve facial rejuvenation procedures. The methodology included an analysis of the existing scientific literature on the individual effects of RF Radiofrequency and IPL, followed by a detailed diagnosis of a 40 – year - old male patient. Treatment consisted of 12 sessions, alternating RF and IPL every three weeks. Skin assessments were performed before and after each session, recording changes in texture, firmness, elasticity and the presence of wrinkles and hyperpigmentation. The results showed significant improvements in the skin of the patient. After the IPL sessions, there was a reduction in areas of hyperpigmentation and a more even texture. The RF sessions contributed to increased skin firmness and elasticity, with a noticeable reduction in the depth of wrinkles and fine lines. The combination of both techniques provided comprehensive skin rejuvenation, with minimal transient adverse reactions such as: redness and mild sensitivity. In conclusion, alternating RF and IPL is an effective and safe strategy for facial rejuvenation in men in their 40s, the approach not only improves aesthetic appearance, but also offers long - lasting benefits by stimulating collagen production and improving skin texture and tone.